Ways To Improve Social Skills In Student - Rozmatova Maftuna Azizjon kizi (Euro Asian Journal Publishing, 2024)
In this article, social competence is studied as a pedagogical problem, and its content, purpose, and the need to improve it in future pedagogues are discussed. The analysis of social competence literature and the research methodology of its research are described, and the principles, methods and means of developing social competence in future pedagogues are defined
Keywords: competence; freedom; social competences